Penerapan Datamining Asosiasi Pada Sistem Persediaan Kosmetik (Kasus Toko Atom Cosmetic Pematangsiantar) - Dinda Zhila Azhari; Sinta Dwi Hastuti (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
The purpose of this research is to find out whether the aamination method with the a priori method can be applied to the cosmetics inventory system at toko atom cosmetic pematangsiantar. The data is sourced from toko atom cosmetic pematangsiantar by conducting interviews with owners and analyzing several sales transactions over the past 1 months. The results of the application of a priori algorithms to the Datamining technique are very efficient and can accelerate the process of forming the pattern pattern of the combination of items from the sale of cosmetic products in the atomic cosmetics store Pematangsiantar, namely with the highest support and confidence are Bedak Wardah - Wardah Foundation and Wardah Foundation - You BB Coushion.